2023
DOI: 10.25073/2588-1094/vnuees.4199
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Evolution of Sandy Island in Front of the Thu Bon River Mouth, Quang Nam Province

Abstract: The main objective of this paper is to investigate the mechanism of formation and evolution of a river mouth island in front of Cua Dai - a mouth of Vu Gia - Thu Bon river system. The combination of coastal morphodynamic analysis with remote sensing, mapping and GIS methods has shown that the formation and evolution of this island depends on a long-term and complex interaction between the dynamics of the Vu Gia - Thu Bon river system and the coastal littoral, including the Cu Lao Cham archipelago. This process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Some studies have shown that the evolution of dunes can follow the trend of gradually moving closer to the northern shore of Cua Dai eroding over time and then disappearing in the absence of major floods in the area. The Thu Bon river system and wave and flow regime are normal as before 2017 (Cham, 2019;Vu Van Phai, 2023). However, the results of the process of combining field measurement data in 2009, 2019, 2020, and 2023 with images obtained from satellite images show that dunes tend to expand to the West, gradually moving inward and down south of Cua Dai.…”
Section: Results and Discussmentioning
confidence: 99%
“…Some studies have shown that the evolution of dunes can follow the trend of gradually moving closer to the northern shore of Cua Dai eroding over time and then disappearing in the absence of major floods in the area. The Thu Bon river system and wave and flow regime are normal as before 2017 (Cham, 2019;Vu Van Phai, 2023). However, the results of the process of combining field measurement data in 2009, 2019, 2020, and 2023 with images obtained from satellite images show that dunes tend to expand to the West, gradually moving inward and down south of Cua Dai.…”
Section: Results and Discussmentioning
confidence: 99%